Life History Study on Witchcraft Victims - Manu, Mieke Yen; Thoomaszen, Friandry W; Hana, Asri Tanggu (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This study aimed to investigate the stories of witchcraft victims in depth. With the case study method in the form of a life history study, research data is reported using thematic analysis to answer research questions. The source of the research data is an informant who is domiciled in the city of Kupang and fits the criteria that have been established. Christian theology provides the primary basis for discussing the research results, while psychology contributes as a complementary viewpoint. The findings indicated that the informants are subjected to a physical ailment accompanied by psychological symptoms and that negative emotions prevail among the informants, leading to a diminished level of well-being.Despite the informant's unfavorable psychological condition, the interplay of appreciation with familial, social, and spiritual support can offer informants experiencing sickness a sense of positive significance. The informants sought deliverance through spiritual support, seeking exorcisms from servants of God, traditional massagers, and shamans. The study’s findings demonstrated that the informants had a gradually positive psychological condition. Still, spiritual camouflage was automatically built to avoid repeating comparable paranormal issues. However, rare and speculative cases of witchcraft are experienced by church members. Therefore, specific assistance by pastors, Christian counselors, psychologists, and/or psychiatrists is highly required as a follow-up action so that victims achieve targeted release and minimize adverse consequences that may occur post-witchcraft.